A sustentabilidade segundo as certificações do sistema LEED: edifícios corporativos em São Paulo (2007-2017) - Passos, Luisa Sapienza (2019)
The present study intends to problematize the sustainability of green certification LEED (Leadership in Energy and Environmental Design), with a research directed to corporate buildings in São Paulo. According to the National Environmental Defense Council, environmental certification are seals that can transmit how the edifications are environmentally responsible. Also selected as eco-labels, the stamps have a classification character and a prudent favor with the planet, life and natural resources. Understanding a particularity of corporate ventures, one instantly perceives the economic and financial interests that fit into the architectural designs developed in parallel to the green stamps. Guiding the technical, economic and market aspects of this practice, the research brings case studies of certified buildings and checks all the credits and categories of the green stamp, understanding your insertion in corporate architecture and analyzing if a certification is capable of determining a building as sustainable.